Analisis Faktor Kedisiplinan Kerja Pegawai Pada Badan Perencanaan Pembangunan Daerah (Bappeda) Kabupaten Lombok Barat - Sudarta, Sudarta; tri Yunarni, Baiq Reinelda; Iswanto, Dedy; Junaidi, Junaidi (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to determine the factors that influence employee discipline in the Regional Development Planning Agency Office of West Lombok Regency. This research is descriptive with a qualitative approach. Data collection was carried out by means of interviews, observation, and documentation. Meanwhile, the analysis technique uses an interactive model consisting of data reduction, data presentation, and drawing conclusions. From the results of the author's observations and interviews at the West Lombok Regency BAPPEDA office, it can be said that all employees and leaders have been deemed to have properly applied discipline in accordance with the applicable regulations according to the State Civil Apparatus Law and the internal regulations of the West Lombok Regency BAPPEDA. There are several factors that affect the work discipline of employees at the West Lombok Regency BAPPEDA Office including the influence factor of compensation, the exemplary factor of the head of the Office, the factor of assertiveness of the leader / head in making decisions, the factor of concern for employees and penalties. Therefore the authors provide several suggestions including the management of BAPPEDA West Lombok Regency to improve employee work discipline by paying more attention to legal sanctions, and paying attention to leadership factors, so that with good leadership and supervision carried out by the leadership regularly, the discipline of employee work at BAPPEDA. West Lombok Regency will be able to be achieved according to the predetermined target so that every employee can make the most of their work time.